Upaya Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan Universitas Gadjah Mada dalam penanggulangan banjir di Kota Bima dengan teknologi pemanen air hujan - Sutono Sutono; Bayu Fandhi Achmad; Citra Indriani; Dyah Ayu Wulansari; Agus Salim Arsyad; Hari Kusnanto; Agus Maryono; Rifqi Amrillah Abdi (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Flood disaster in Bima Town, West Nusa Tenggara Province, Indonesia at the end of 2016 affected 105,753 people. For the period of the disaster, water flooding whole area of the town. Universitas Gadjah Mada (UGM) represented by Faculty of Medicine, Public Health, and Nursing supported by the Faculty of Medicine Alumni Association (KAGAMADOK) sent two response teams to the disaster area with the aims to assess health status of the refugees and to create rainwater harvesting tool. There were two teams assigned to the flood management in Bima. First team assigned to establish database and health cluster information analysis, performed needs assessment at refugee camp and affected area, and sent the patient to emergency health service. Regarding to the first team assessment results, second team assigned to create rainwater harvesting tool. First UGM team discovered that communities experiencing high prevalence of dermatology disease, meanwhile the medicine livestock diminished. Escalation of diarrhea cases especially in children and limited community health surveillance in Bima Town were also identified by the team. The second team was in a mission to accomplish environmental studies associated with flood disaster and implement rainwater harvesting technology. Rainwater harvesting technology implemented based on data collection and analysis from the first team. Rainwater harvesting technology used to supply community water necessities since the groundwater in disaster area remain muddy and smells. Application of rainwater harvesting equipment completed at Penanae and Mpunda Primary Health Care. Deployment of the UGM Bima disaster response team expected to spring positive benefits to the flood affected communities, and in addition expected that the assistance from UGM established sustainably.